THE GENEVAN PSALMS (1562) IN THE HUNGARIAN CHORAL LITERATURE - Éva PÉTER (Studia Universitatis Babeş-Bolyai. Musica)
At the middle of the 20th century in a time of the upturn of the general musical culture Hungarian composers having experience with ecclesiastical music created adaptations of various levels of difficulty for the tunes of the Genevan psalms. In 1979 a representative volume entitled Hungarian Psalms edited by Sándor Arany was created, a volume that contained the adaptations. Selecting from this volume I would mention Jenő Ádám’s 8. Psalm, Lajos Bárdos’s 23. Psalm, Zoltán Kodály’s 50. Psalm and 114. Psalm.